Health literacy and behavior related to cancer and diabetes among higher secondary students - Rahim, Zahidur; Makkia, Fatima Tuz Zohra; Haque, Md Ekramul; Robin, TA; Debnath, Sumon Chandra; Rouf, Md Abdur; Hasan, Dewan Md Mehedi; Chowdhury, Zobaid Mohammad Rahat (Asian Journal of Medical and Biological Research, 2017)
This cross sectional study was carried out among 313 higher secondary college students to assess the knowledge on health literacy and behaviors related to non communicable diseases (Diabetes and Cancer). The study period was from January to December 2013. Majorities (63%) of the respondents were male and rests of them (37.0%) were female. Maximum of the (45.1%) respondent’s father was higher educated (masters) and more than one-third (34.9%) mothers were graduate. A vast majority (98.1%) of the respondents indicated smoking as the main risk factor for Cancer in which most (89.8%) of the respondents mentioned excess body weight as the most important risk factor for Diabetes. A vast majority (93.9%) of the respondents gave emphasis about cessation of tobacco for the prevention of cancer whereas majority (79.9%) of the respondents gave emphasis about physical exercise and labor for the prevention of Diabetes. Knowledge about health literacy is statistically significant (p=0.021) with gender of the students. Father and mother educational status were not significantly associated (p>0.05) with health literacy. Need based, specific, time relevant and school based programs and community based awareness program need to be designed for further improvement of health literacy among college students. Asian J. Med. Biol. Res. September 2017, 3(3): 341-346